PENGUKURAN KINERJA INSTANSI PEMERINTAH DAERAH DALAM PERSPEKTIF VALUE FOR MONEY - Permana, Dhimas Angga; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out and to analyze the measurement of the Department of Communication andInformation of Surabaya city in 2015 through the Value for Money approach. The research method has beenconducted by using qualitative descriptive with the source of data isthe primary and the secondary data. Theresearch object is the performance of the Department of Communication and Information which is included in theperformance statement (LKJ) ofthe Department of Communication and Information in 2015 periods. Theperformance assessment refers to the input indicator, output indicator, and outcome.The result of this researchshows that the Department of Communication and information of Surabaya city from economic aspects refers tothe budget (input)and budget realization. The efficiency assessment can be seen from the numbers of outputrealizations which have been generated to the input. Meanwhile, the effectiveness measurement can be seen fromthe output or even outcome which have been assessed and based on the institution objectives in implementingprograms and activities by using standard of economic, efficiency, and effective. In assessing the performanceeffectiveness it is required to pay attentionto the advantages which have been achieved by the public whohavereceived the benefit of the implemented program.Keywords: Performance, value for money, economic, efficiency, effectivity.